A Topology Structure Based Outer Membrane Proteins Segment Alignment Method. (26th October 2013) - Wang, Han; Liu, Bo; Sun, Pingping; Ma, Zhiqiang
Abstract : Outer membrane proteins (OMPs) are transmembrane proteins (TMPs) located in outer membranes. These proteins perform diverse biochemical functions and have immediate medical relevance, so that their spatial structures are important for studying. But the special physicochemical properties of OMP make it hard to obtain their structures experimentally. For the purpose of predicting OMP structures, discriminating OMPs and aligning their sequences to native structures are indispensable steps. We developed a novel method OMSA (Outer Membrane Segment Alignment), which implemented both steps in one program. OMSA integrates OMP-specific topology features to implement a sequence-to-structure alignment, for example, segment type and segment orientation, while a segment-dependent gap penalty model is employed to improve the alignment. Compared to peer top-leading methods, OMSA achieved higher accuracy in both OMP discrimination and alignment, which may further improve OMP structure studying.